Etika Profesi dan Profesionalisme Public Relations - I Dewa Ayu Hendrawathi Putri; Ni Ketut Sri Ratmini (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2017)
Professional Ethics emphasis on human relationships with others who have the same profession. The goal, so there is a good cooperation and alignment between one individual with another individual in the same profession. Ethics in Public Relations have the same goal with the ethics of the profession. Their ethics Public Relations No alignment is expected to lead to good cooperation between individuals within the scope of Public Relations and improve the professionalism of practitioners of Public Relations. A professional in performing their duties and obligations are always closely related to the code of ethics (code of profession) and codes of conduct (code of conduct) as moral standards, benchmarks or guidelines in carrying out the work and responsibilities of each in accordance with its function and role in the organization represents. In addition, a public relations professional must be able to work or to act through a thorough consideration and correct. A professional can distinguish ethically which can be done and what can not be done according to the guidelines of the code of professional conduct that is carried by the person concerned